2013
DOI: 10.1124/mol.112.082743
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib-Mediated Cyclooxygenase-2 Expression via Epidermal Growth Factor Receptor/HuR Interaction Enhances the Aggressiveness of Triple-Negative Breast Cancer Cells

Abstract: Lapatinib, a dual epidermal growth factor receptor (EGFR)/human epidermal growth factor receptor 2 (HER2) kinase inhibitor, showed clinical benefits in advanced HER2-positive breast cancer patients. Because some triple-negative breast cancers (TNBCs) frequently overexpress EGFR, the antitumor activity of lapatinib in such diseases was also tested. However, the results showed a worse event-free survival rate. It remains unknown whether and how lapatinib elicits the aggressiveness of such cancer cells. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
4
31
0
3
Order By: Relevance
“…Furthermore, recent work performed with human breast cancer cell lines suggested that LapatinibÔ (LC Laboratories, Woburn, Massachusetts, USA), a dual EGFR/HER2 kinase inhibitor, may increase the migration and invasion of cells by up-regulating There is a significant association between COX-2 and EGFR expression (P ¼ 0.001). EGFR and COX-2 (Hsia et al, 2013). These findings and the evidence that 25.5% of tumours in the present study showed high expression of COX-2 and EGFR, emphasizes the need for additional studies with selective inhibitors of the two molecules in order to verify their true clinical effectiveness in CMTs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, recent work performed with human breast cancer cell lines suggested that LapatinibÔ (LC Laboratories, Woburn, Massachusetts, USA), a dual EGFR/HER2 kinase inhibitor, may increase the migration and invasion of cells by up-regulating There is a significant association between COX-2 and EGFR expression (P ¼ 0.001). EGFR and COX-2 (Hsia et al, 2013). These findings and the evidence that 25.5% of tumours in the present study showed high expression of COX-2 and EGFR, emphasizes the need for additional studies with selective inhibitors of the two molecules in order to verify their true clinical effectiveness in CMTs.…”
Section: Discussionsupporting
confidence: 53%
“…In human cancer, several studies have focused on these molecules, mainly in lung and oesophageal adenocarcinomas, non-small cell lung cancer and nasopharyngeal, colonic, colorectal and cholangiocarcinomas (Pai et al, 2003;Ceccarelli et al, 2005;Han and Wu, 2005;Li et al, 2006;Van Dyke et al, 2008;Huang et al, 2010;Li et al, 2011). In contrast, there are fewer studies of these molecules in human breast cancer (Lanza-Jacoby et al, 2006;Hsia et al, 2013). In the dog, to the best of our knowledge, no studies have investigated the association between COX-2 and EGFR expression in mammary tumours.…”
Section: Introductionmentioning
confidence: 95%
“…Lapatinib has recently been found to up-regulate the gene expression of proapoptotic TRAIL death receptors DR4 and DR5 [21]. Our recent study also showed that lapatinib can induce the NF-κB-targeted gene COX-2 in a HER2/EGFR-independent manner [22]. These observations raise the possibility that lapatinib may increase NF-κB activity independently of targeting EGFR and HER2.…”
Section: Introductionmentioning
confidence: 63%
“…Hsia et al presented lapatinib-mediated upregulation of aggressiveness in breast cancer cells [26]. Lapatinib, a dual epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) kinase inhibitor, is used for the treatment of advanced HER2-positive breast cancer [27].…”
Section: Rbps and Drug Resistancementioning
confidence: 99%